Adaptive Mode Control Strategy of a Multimode Hybrid Energy Storage System. (June 2016) - Wang, Bin; Xu, Jun; Cao, Binggang; Li, Qiyu; Yang, Qingxia
Abstract: To improve the efficiency of the multimode hybrid energy storage system (HESS), a novel adaptive mode control strategy (ADCS) based on logic threshold and hysteresis control strategy is proposed. The operating modes of the multimode HESS are first analyzed. Then, the adaptive target voltage of the ultracapacitor and the adaptive goal function are established. On this basis, the ADCS is designed. At last, the simulation model is established in Matlab. Simulation results show that the multimode HESS with the ADCS can avoid the excessive output power of the lithium battery and the UC absorbs all the braking energy, which ensures the battery safety. Compared to the logic threshold and hysteresis control strategy, the ADCS can obviously improve the overall system efficiency of the multimode HESS.